Mast Cell Inhibition Attenuates Myocardial Damage, Adverse Remodeling, and Dysfunction During Fulminant Myocarditis in the Rat. (March 2013) - Mina, Yair; Rinkevich-Shop, Shunit; Konen, Eli; Goitein, Orly; Kushnir, Tammar; Epstein, Frederick H.; Feinberg, Micha S.; Leor, Jonathan; Landa-Rouben, Natalie
Background: Myocarditis is a life-threatening heart disease characterized by myocardial inflammation, necrosis, and chronic fibrosis. While mast cell inhibition has been suggested to prevent fibrosis in rat myocarditis, little is known about its effectiveness in attenuating cardiac remodeling and dysfunction in myocarditis. Thus, we sought to test the hypothesis that mast cell inhibition will attenuate the inflammatory reaction and associated left ventricular (LV) remodeling and dysfunction after fulminant autoimmune myocarditis. Methods and Results: To induce experimental autoimmune myocarditis, we immunized 30 rats with porcine cardiac myosin (PCM) twice at a 7-day interval. On day 8 animals were randomized into treatment with either an intraperitoneal (IP) injection of 25mg/kg of cromolyn sodium (n = 13) or an equivalent volume (∼0.5 mL IP) of normal saline (n = 11). All animals were scanned by serial echocardiography studies before treatment (baseline echocardiogram) and after 20 days of cromolyn sodium (28 days after immunization). Furthermore, serial cardiac magnetic resonance was performed in a subgroup of 12 animals. After 20 days of treatment (28 days from first immunization), hearts were harvested for histopathological analysis. By echocardiography, cromolyn sodium prevented LV dilatation and attenuated LV dysfunction, compared with controls. Postmortem analysis of hearts showed that cromolyn sodium reduced myocardial fibrosis, as well as the number and size of cardiac mast cells in the inflamed myocardium, compared with controls. Conclusions: Our study suggests that mast cell inhibition with cromolyn sodium attenuates adverse LV remodeling and dysfunction in myocarditis. This mechanism-based therapy is clinically relevant and could improve the outcome of patients at risk for inflammatory cardiomyopathy and heart failure.